Impact of technological change on communication climate in a higher learning institution : A case of IIUM free wireless connection - Ilfandy, Ayub; Wok, Saodah (2011)
 Innovation – New, novelty, better discovery and invention  Technological innovation resulted from installation, improvement, modification or replacement of current available technology.  Implementation of technological change normally affects the organization work system and its operation, effectiveness, productivity while giving comfort to organizational members. Thus, resulting organization change.